Newton polytope of good symmetric polynomials - Duc-Khanh Nguyen (2023)
We introduce a general class of symmetric polynomials that have saturated Newton polytope and their Newton polytope has integer decomposition property. The class covers numerous previously studied symmetric polynomials.